Development of effective modified palm shell waste-based activated carbon adsorbents for pollutants removal / Farahin Mohd Jais - Farahin , Mohd Jais (2017)
A simple and cost-effective water/wastewater treatment was approached by adsorption technique. While, palm shell-waste based activated carbon widely used in variety field and available in abundance in Malaysia. It was chosen as the basic raw adsorbent before modification can be made. In order to achieve high adsorption performance, special modification of adsorbent need to be made based on types of pollutant to be removed which are in this study, Arsenic removal from groundwater and Methyl Orange & Methylene Blue dye from textile wastewater. The first modification of Palm Shell waste–based Activated Carbon (PSAC) is for removal of Arsenate ion was synthesized through dual modification. At first, Magnetic Palm Shell waste-based Activated Carbon (MPSAC) was developed via hydrothermal impregnation of nano–magnetite, and secondly it was coated by various amounts of lanthanum (La) followed by calcination. Numerous batch tests were carried out to observe arsenate removal performance. Isotherm data showed that MPSAC–La(0.36) (weight ratio of La to Fe = 0.36) gave the highest adsorption capacity (227.6 mg g–1), which was 16.5 and 1.6 times higher than PSAC and MPSAC, respectively. Based on the pH effect and speciation modeling, arsenate was predominantly removed by precipitation at pH < 8, while it complexed on the surface of La(OH)3 at pH > 8. Lesser La dissolution resulted, owing to a strong binding effect of nano–magnetite with La. XRD, FTIR, FESEM+EDX, and N2 gas isotherms showed that the coating of nano–magnetite introduced substantial clogging in the micropores of PSAC, but increased meso– and macropores. However, lanthanum oxide/hydroxide (LO/LH) glued the spaces of nano–magnetite to eliminate most pore structures, and effectively removed arsenate as LaAsO4 at pH 6. The second modification of PSAC is for Methyl Orange and Methylene Blue dye was developed through triple modification. First, magnetized PSAC (MPSAC) was developed through film coating method followed by second method, co-precipitation to coat MPSAC with SiO2, which acted as template for MgCO3 crystalline structure. The MPSAC-SiO2 was then undergo third modification, hydrothermal impregnation method with different molar ratio, MgNO3: urea proceed with calcination to form MPSAC-SiO2@MgNO3. Several batch studies were completed to compare the adsorption performance. The isotherm tests show MPSAC-SiO2@MgNO3(0.46) with highest MgNO3 molar ratio gave the highest Methyl Orange adsorption capacity, Qmax=1091.6 mg g-1 which about 2.7 times higher than PSAC, 378.37 mg g-1. While, it only gave 471.82 mg g-1 Methylene Blue removal capacity which was 1.15 times higher than PSAC, 409.54 mg g-1. Meanwhile, pH studies reported MPSAC-SiO2@MgNO3(0.46) capable to remove both dye at high capacity at most pH range. Through triple modification, XRD, FTIR, FESEM+EDX, and N2 gas isotherms analysis reported micropore structure was reduced, blocked and eventually disappeared after dye was loaded on adsorbent surface caused morphological changed indicated high accumulation of adsorbed dye on the surface. To conclude, both modified MPSAC–La(0.36) and MPSAC-SiO2@MgNO3(0.46) are considered as new competitive granular materials due to its high sorption capabilities, easy magnetic separation and high regeneration rate for both types of pollutant.